G58(P) Multi-agency review of child protection medical reports. (27th April 2015) - Wilson, IE; Lee, B; Elliman, D
Abstract : The RCPCH Child Protection Companion provides guidance on medical report writing. We wanted to audit local medical reports against this guidance. Reports are shared with social care and police child abuse investigation team (CAIT), contributing to decision making for children. We therefore wished to determine whether our local social care and CAIT teams felt the opinions in the reports were helpful to their decision making. A retrospective audit of reports of 24 children seen in the first half of 2014 was undertaken, using section 16 of the RCPCH companion as standards. 3 reports from each of the 8 consultants were chosen at random. CAIT and social care reviewed the same 24 reports and completed a proforma regarding key aspects of the medical opinion. Patients' details, consultation time/place, specific concerns, appearance of the child, past medical, family and developmental history were completed in all reports. 75% gave the child's own words where applicable, 89% gave information regarding school/nursery and 64% commented on parent/carer interaction. Most reports commented on the need for section 47 investigation but made no direct statement on whether it was safe for the child to return home. Social care and CAIT thought 19 and 16 reports respectively were helpful in decision making. Reported unhelpful factors were non-committal wording on the likelihood of NAI, ambiguity around sibling cases and lack of documentation regarding evidence for neglect concerns. Clear documentation of patients' and consultation details reflects local strong administrative support. Key areas for child protection, notably the words of the child and child parent interaction were lacking and should be highlighted in training. Paediatricians may have made verbal recommendations during the medical but documentation of this is imperative. The satisfaction of CAIT/social care with reports depends upon their expectations as well as the doctor's clarity. In some cases the doctor could not have given a 'clear' opinion based on what was in front of them. It is valuable for local audits of child protection reports to involve local CAIT and social care to optimise the usefulness of reports in safeguarding of children.